Multidimensional Therapy (Bio, Psycho, Social) of Heroin Abusers (Drug Control Headquarters, Research and Education Office, 2004)
The present article is the report of an experimental research consists of a sample of 30 male heroin addicts who have referred to National Drug Addiction Researches in order to receive medical therapy (methadone) in 1382-83. These individuals (23-34 years old) are studied in two test group (15) and control group (15). Different mental therapy methods (group, family, individual) were applied for this sample. In this research, a questionnaire with 79 questions and a few short checklists was used in order to measure individuals' mental/social characteristics via Post-Test and Pre-Test methods. The validity of this questionnaire was calculated 82 percent after two tests. To analyze the data, two methods were applied: quantitative method (dependent/independent descriptive statistics, test statistics and T statistics) and qualitative method (interview, observation, questionnaire). The findings of qualitative method represented in this article, indicate a meaningful difference between these two groups. It also shows that by applying a holistic approach, treatment process is better and faster and relapse possibility is less if it have been following up for at least one year.